Prevalence of congenital cardiac anomalies in patients with cleft lip and palate - Its implications in surgical management - Akash Kasatwar; Rajiv Borle; Nitin Bhola; Rajanikanth K; G.S.V. Prasad; Anendd Jadhav (Elsevier, 2018)
Background: Cleft lip and palate is one of the most common congenital craniofacial deformities seen in children. Various congenital anomalies are reported in the literature to be associated with cleft lip and palate. Cardiac anomalies are one of the most common congenital disorders associated in cleft lip and palate patientsIt includes Cyanotic and acyanotic cardiac diseases likel fallot's tetralogy, transposition of greater vessels, atresia of tricuspid, total anomalous pulmonary venous return (TAPVR), truncus arteriosus, ebstein's anomaly, hypoplastic left heart syndrome and pulmonary atresia, patent ductus arteriosus, ventricular septal defect, atrial septal defect, pulmonary stenosis, aortic stenosis and coarctation of aorta. Aim: To study the prevalence of congenital cardiac anomalies in cleft lip and palate patients. Objectives: To study different types of congenital cardiac anomalies/defects in patients with cleft lip and palate and its implications in surgical management. Materials and Methods: This is a retrospective study carried out for a period of one year. In the present study medical records of 200 patients with cleft lip and palate were evaluated and analyzed for presence of congenital cardiac anomalies. Results: Out of 200 patients of cleft lip and palate, 30 patients (15%) were associated with congenital cardiac anomalies with male to female ratio of 1:1. Associated congenital cardiac anomalies were most frequently seen in unilateral cleft palate patients (21.05%) The most common cardiac anomaly was Ventricular septal defect (36.6%).